Implikasi Ekologi Lontar Aji Janantaka Terhadap Masyarakat di Desa Marga, Kecamatan Marga, Tabanan, Bali - Ni Wayan Winiantari (Pramana: Jurnal Hasil Penelitian, 2021)
Balinese literature is the result of the creativity and imagination of Balinese writers who have become a culture and preserved from generation to generation, which usually uses the Balinese language as a medium of communication and includes the social life of the Balinese people. Speech is one type of ancient Javanese literary work that contains philosophical, religious, and life values. Literary works in this type of speech besides containing the value of religious philosophy in it also reflect a local wisdom of the Balinese people which until now has been used as a way of life. This research is classified as a qualitative research, carried out in Marga village, Marga sub-district, Tabanan district, Bali. Primary data is Lontar Aji Janantaka, while secondary data in this study are data and informants who know and understand about Lontar Aji Janantaka and plants in Marga village, as well as books and journals related to Lontar Aji Janantaka and plants. The results of this study indicate that Aji Janantaka is a speech which basically describes the types of trees affected by Cukil Daki disease and various flower plants that receive the gift of cleansing. In utilizing plants in everyday life, the teachings or education contained in Aji Janantaka's lontar can have a positive impact on society in various fields. Lontar Aji Janantaka can be used as a reference for the Marga village community both in social life.